2016
DOI: 10.1177/0194599816684098
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology Education: Recent Trends in Publication

Abstract: Objectives (1) Evaluate peer-reviewed publications regarding education in otolaryngology since 2000. (2) Analyze publication trends as compared with overall otolaryngology publications. Study Design Bibliometric analysis. Setting Academic medical center. Subjects and Methods A search for articles regarding education in otolaryngology from 2000 to 2015 was performed with MEDLINE and EMBASE databases, yielding 1220 articles; 362 relevant publications were categorized by topic, subspecialty, subject, article type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…High quality education research serves to enhance clinical practices and careers of current trainees and surgical educators. A 2016 bibliometric analysis identified that publications in OHNS education increased rapidly from 2000 to 2015 with education articles being published more frequently in higher-impact OHNS journals [ 14 ]. Furthermore, OHNS education research can also be published in education-focused (non-OHNS) journals with high impact factors.…”
Section: Discussionmentioning
confidence: 99%
“…High quality education research serves to enhance clinical practices and careers of current trainees and surgical educators. A 2016 bibliometric analysis identified that publications in OHNS education increased rapidly from 2000 to 2015 with education articles being published more frequently in higher-impact OHNS journals [ 14 ]. Furthermore, OHNS education research can also be published in education-focused (non-OHNS) journals with high impact factors.…”
Section: Discussionmentioning
confidence: 99%
“…10 When looking at publishing trends over time, there has been a significant increase in publications after 2009, which could be due to various factors including a general increase in research in the past decade. 31,32 The concomitant increase in authors may be due to a greater interest in collaboration between different institutions and may reflect the growing interest in this topic. There was a nonsignificant increase in female authorship perhaps reflecting an overall larger representation overall of females in surgical fields including otolaryngology than in the past or the increasing number of women in academic medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In the classification made according to subjects both pediatrics and adults, the field of otology was at the forefront. [7][8][9][10] Otology publications showing a tendency to genetic, microbiological, and pathological studies were of areas which have not yet been fully resolved and are open to innovations such as hearing loss, tinnitus and dizziness, developments, especially endoscopic, in surgery, developments and widepread use of surgery in the approaches to hearing loss, and the provision of opportunities for animal studies. When diseases encountered in daily practice are evaluated, otolaryngology practice is generally formed of otological and rhinological diseases.…”
Section: Discussionmentioning
confidence: 99%